The Effect of Advertising Attractiveness on Purchase Intention on Taobao E-Commerce With Brand Image as an Intervening Variable Reviewed in Islamic Business Perspective (Case Study on Generation Z in Taiwan) - Maynia Rahmawati; Muhammad Iqbal; Okta Supriyaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of advertising attractiveness on purchase intention in Taobao e-commerce, with brand image as a mediating variable. A quantitative approach was employed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire completed by 100 respondents aged 15–30 years in Taiwan who have a Taobao account, have shopped online, and are familiar with or have used the Taobao website. Based on the background of this article, the method used in this study is a descriptive method with a quantitative approach. Data were obtained through research on Generation Z in Taiwan. The results indicate that advertising attractiveness has a positive and significant influence on both brand image and purchase intention. Furthermore, brand image mediates the relationship between advertising attractiveness and purchase intention. These findings suggest that advertising attractiveness enhances interactive shopping experiences and builds a strong consumer perception of the brand in online shopping. From an Islamic business perspective, advertising attractiveness contributes to transparency and honesty, thereby increasing purchase intention. This study recommends further development of advertising features to make them more realistic in order to maximize their effectiveness in digital marketing.